Sistem Pendukung Keputusan dalam menentukan Guru Teladan menggunakan Metode Composite Performance - Hidayanti, Sri; Mulyani, Neni; Ramadhani, Andrew (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The development of technology has had a significant impact on various aspects of human life, including education. Yayasan Mas Bustaanul Uluum, a high school, faces challenges in selecting exemplary teachers objectively and accurately. The process of selecting exemplary teachers has so far been subjective, with assessments based on attendance and years of service. This research aims to develop a decision support system (DSS) by applying the web-based Composite Performance Index (CPI) method. The system is built using the waterfall model, which consists of analysis, design, implementation, and testing. Data collection was conducted through observation and interviews. The aspects used to measure exemplary teachers include attendance, teaching experience, highest education level, and achievements. The data processed using the CPI method is used to determine exemplary teachers. Furthermore, the system built was tested using black box testing on each system component. Our findings resulted in a DSS integrated with the CPI method for determining exemplary teachers. The calculations within the system are also consistent with the manual calculations using the CPI method. Additionally, the system operates smoothly without errors. Therefore, this system can assist Yayasan Mas Bustaanul Uluum in selecting exemplary teachers in an objective manner.